2016
DOI: 10.1007/s00417-016-3536-2
|View full text |Cite
|
Sign up to set email alerts
|

Modified lateral tarsal strip for involutional entropion and ectropion surgery

Abstract: The modified suture placement of the tarsal strip reported in this work improves the lower eyelid stability and prevents future recurrences after surgery. This modified technique is useful for the management of patients with entropion and moderate eyelid dysfunction retractors without other surgical procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 35 publications
0
34
0
3
Order By: Relevance
“…The modified suture placement of the tarsal strip improved the lower eyelid stability and prevented recurrences after surgery. The modified LTS technique is helpful for the management of patients with entropion and ectropion 14 . Patients treated with double sutures and conjunctival cuts in the LTS showed lower horizontal laxity (3.5 ± 0.2) than patients treated with Conventional LTS (5.7 ± 0.2).…”
Section: Discussionmentioning
confidence: 99%
“…The modified suture placement of the tarsal strip improved the lower eyelid stability and prevented recurrences after surgery. The modified LTS technique is helpful for the management of patients with entropion and ectropion 14 . Patients treated with double sutures and conjunctival cuts in the LTS showed lower horizontal laxity (3.5 ± 0.2) than patients treated with Conventional LTS (5.7 ± 0.2).…”
Section: Discussionmentioning
confidence: 99%
“…The LTS group showed a recurrence rate of 11.5% at 12 months, higher than the recurrence rate of the combined procedure (ES + LTS) which was 0% at 18 months in the study by Scheepers et al [21] and 9.4% at 24 months in the study by Ho et al [22]. Published data shows that the recurrence rate of the LTS procedure alone varies from 14–22% while López-García et al reported a rate of 4% for a modified LTS technique [2325].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we describe a new approach based on Hill’s procedure in involutional entropion with documented eyelid laxity in the Chinese population. LTS is a popular procedure for eyelid shortening and can be used either in entropion or ectropion correction [7, 9]. Although LTS is effective in tightening the eyelid, it is known to have disadvantages such as under correction, webbing, recurrence and disruption of the lateral canthal angle [20, 21].…”
Section: Discussionmentioning
confidence: 99%
“…Although LTS is effective in tightening the eyelid, it is known to have disadvantages such as under correction, webbing, recurrence and disruption of the lateral canthal angle [20, 21]. López-García et al [7] reported recurrence rate of 17.4% after conventional tarsal strip surgery for involutional entropion. It can be combined with other procedures such as everting sutures [13, 14, 17] and inferior retractor plication, shortening or advancement [12, 18, 19].…”
Section: Discussionmentioning
confidence: 99%